2024
DOI: 10.1007/s00246-024-03449-1
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Responsiveness in a Cohort of Pediatric Patients with Right Ventricle to Pulmonary Artery Conduits and Transcatheter Valve Replacement Systems

Sean T. Kelleher,
Irene E. Regan,
Dermot Cox
et al.

Abstract: The aim of this study was to determine the rate of aspirin responsiveness in a cohort of pediatric patients with in situ xenograft valved right ventricle to pulmonary artery (RV-PA) conduits and/or transcatheter valve replacements (TVR). Aspirin is routinely prescribed to these patients. Optimizing anti-platelet therapy could promote valve longevity and reduce the risk of infective endocarditis in this at-risk group. This was a prospective, observational study. Patients were recruited from both ward and outpat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Habib et al reported that aspirin thromboprophylaxis before the onset of cardiovascular implantable electronic device-related bloodstream infection was associated with a lower likelihood of vegetation formation on the device [23] and in a similar manner, Eisen et al concluded that aspirin usage was associated with a reduced risk of emergency valve replacement surgery in patients with Staphylococcus aureus-associated infective endocarditis [25]. As a result of the high prevalence of reduced response to aspirin in this sub-cohort, patients with RV-PA conduits were followed up in a subsequent institutional study [26]. Three patients (12.5%) in Q1 and Q2 (n = 3/24) had suboptimum responses to aspirin had Fontan conduits.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Habib et al reported that aspirin thromboprophylaxis before the onset of cardiovascular implantable electronic device-related bloodstream infection was associated with a lower likelihood of vegetation formation on the device [23] and in a similar manner, Eisen et al concluded that aspirin usage was associated with a reduced risk of emergency valve replacement surgery in patients with Staphylococcus aureus-associated infective endocarditis [25]. As a result of the high prevalence of reduced response to aspirin in this sub-cohort, patients with RV-PA conduits were followed up in a subsequent institutional study [26]. Three patients (12.5%) in Q1 and Q2 (n = 3/24) had suboptimum responses to aspirin had Fontan conduits.…”
Section: Discussionmentioning
confidence: 66%
“…A proposed algorithm for testing is outlined in Fig. 3, adapted from our earlier study [26]. There has been much debate on the relationship between aspirin dose and treatment effect, particularly in adult populations [32,33] but more recently in pediatric patients [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation